The Effect of Return on Assets, Current Ratio, Debt to Equity Ratio, and Company Size on Firm Value : A Study on Telecommunications Sub-Sector Companies in Indonesia - Kroy, Monica; Desmiza (Indonesian Scientific Publication, 2025)
This research examines the worth of businesses in Indonesia's telecommunications industry, a crucial area of the economy that has seen considerable expansion. Changes in company value within this field, frequently tied to fluctuating stock prices, prompt inquiries into the key factors at play. The aim of this research is to evaluate how return on assets (ROA), cash-to-assets ratio (CR), debt-to-equity ratio (DER), and company size affect the value of telecommunications firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Employing a descriptive associative quantitative method, this study investigates panel data from 12 telecommunications firms chosen using purposive sampling from a total of 22. Panel data regression analysis was performed utilizing EViews 13 software. The findings reveal that return on assets (ROA) has a meaningful positive effect on company value. In contrast, the debt-to-equity ratio (DER) significantly harms company value. The liquidity ratio (CR) and company size, however, do not exhibit significant partial impacts. Overall, ROA, CR, DER, and company size do affect firm value. This research concludes that ROA and capital structure (DER) are vital elements in influencing the worth of telecommunications companies. It is recommended that these companies enhance ROA through efficient asset use and effectively manage DER to boost investor trust and company value in a competitive environment.